Job strain and effort-reward imbalance as risk factors for type 2 diabetes mellitus: A systematic review and meta-analysis of prospective studies - Ana Paula B Pena-Gralle; Denis Talbot; Caroline S Duchaine; Mathilde Lavigne-Robichaud; Xavier Trudel; Karine Aubé; Matthias Gralle; Mahée Gilbert-Ouimet; Alain Milot; Chantal Brisson (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVES: This systematic review and meta-analysis aimed to synthesize the available data on prospective associations between work-related stressors and the risk of type 2 diabetes mellitus (T2DM) among adult workers, according to the demand-control-support (DCS) and the effort-reward imbalance (ERI) models. METHOD: We searched for prospective studies in PubMed, EMBASE, Web of Science, Scopus, CINHAL and PsychInfo. After screening and extraction, quality of evidence was assessed using the ROBINS-I tool adapted for observational studies. The effect estimates extracted for each cohort were synthesized using random effect models. RESULTS: We included 18 studies (reporting data on 25 cohorts) in meta-analyses for job strain, job demands, job control, social support at work and ERI. Workers exposed to job strain had a higher risk of developing T2DM when compared to unexposed workers [pooled rate ratio (RR) 1.16, 95% confidence interval (CI) 1.07-1.26]. This association was robust in several supplementary analyses. For exposed women relative to unexposed women, the RR was 1.35 (95% CI 1.12-1.64). The RR of workers exposed to ERI was 1.24 (95% CI 1.08-1.42) compared to unexposed workers. CONCLUSIONS: This is the first meta-analysis to find an effect of ERI on the onset of T2DM incidence. It also confirms that job strain increases the incidence of T2DM, especially among women.